Evaluating visitor's satisfaction towards facilities and services in National Elephant Conservation Centre, Kuala Gandah, Pahang - Ahmad Jihaduddin, Ahmad Aiman (2016)
Visitors evaluation is important for any recreation place to carry out research. Visitors evaluation research also important to know the satisfication level of visitors on the place. In this way, we can know the weaknesses of certain area of the place to be repaired. This study was conducted in National Elephant Kuala Gandah (NECC), Lanchang, Pahang to evaluate visitors‟ satisfaction towards facilities and services provided at NECC. One hundred respondents were interviewed using a structured questionnaire based on convenience sampling technique. The questionnaire consists of three parts (1) socio demographic, (2) visitors‟ satisfaction towards facilities, and (3) visitors‟ satisfaction towards services at NECC. Index of satisfaction towards facilities and services provided by NECC were calculated. Mann-Whitney and Kruskal Wallis test were used to determine any significant differences of satisfaction of selected sosio-economic variables levels. The results show that, most of the visitors to NECC were satisfied with the facilities and services provided. It was also founded that, age, nationality, income and marital status were the significant factors influencing visitors‟ satisfaction. Suggestions on the improvement,one or more staff should be employed as nature interpreters for the visitors. This will increase visitors appreciation of nature.